Kościół N. P. Maryi, dekarz I [fot.] Kazimierz Lelewicz. - Lelewicz, Kazimierz (1896-1986) (1945)
Przedstawia dekarza przy kryciu dachu Kościoła Mariackiego dachówką, w głębi widoczna ul. Piwna, 1950 r.